Cloning and characterization of a pyrethroid pesticide decomposing esterase gene, Est3385, from Rhodopseudomonas palustris PSB-S - Xiangwen Luo (Nature Portfolio, 2018)
Abstract Full length open reading frame of pyrethroid detoxification gene, Est3385, contains 963 nucleotides. This gene was identified and cloned based on the genome sequence of Rhodopseudomonas palustris PSB-S available at the GneBank. The predicted amino acid sequence of Est3385 shared moderate identities (30–46%) with the known homologous esterases. Phylogenetic analysis revealed that Est3385 was a member in the esterase family I. Recombinant Est3385 was heterologous expressed in E. coli, purified and characterized for its substrate specificity, kinetics and stability under various conditions. The optimal temperature and pH for Est3385 were 35 °C and 6.0, respectively. This enzyme could detoxify various pyrethroid pesticides and degrade the optimal substrate fenpropathrin with a Km and Vmax value of 0.734 ± 0.013 mmol·l−1 and 0.918 ± 0.025 U·µg−1, respectively. No cofactor was found to affect Est3385 activity but substantial reduction of enzymatic activity was observed when metal ions were applied. Taken together, a new pyrethroid degradation esterase was identified and characterized. Modification of Est3385 with protein engineering toolsets should enhance its potential for field application to reduce the pesticide residue from agroecosystems.